Local government finance the challenges of the 21st century : second global report on decentralization and local democracy : GOLD II 2010 - United Cities and Local Governments; Edward Elgar Publishing (Cheltenham : Edward Elgar, 2011)
This book, compiled from the 2nd Global Report of United Cities and Local Governments (UCLG) on Decentralization and Local Democracy, analyzes the architecture of fiscal decentralization in one hundred and ten countries as well as in major metropolitan areas. In the majority of these countries, local authorities are taking on more and more responsibilities for public investment and the provision of services that are essential for both economic development and the well being of their citizens.
1. Introduction -- 2. Africa -- 3. Asia-Pacific -- 4. Eurasia -- 5. Europe -- 6. Latin America -- 7. Middle East and Western Asia -- 8. North America -- 9. Financing metropolitan areas -- 10. Conclusion.
Includes bibliographical references.
Keywords: Local finance -- Cross-cultural studies; Electronic books